2011
DOI: 10.1111/j.1540-8159.2011.03229.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents with Implantable Cardioverter Defibrillators: A Patient and Parent Perspective

Abstract: These findings have important implications for clinical practice and may help guide medical management for adolescents with ICDs and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 25 publications
1
38
0
Order By: Relevance
“…Specifically, some parents reported that their children struggled with ''feeling different'' and that they expressed desire to be more like their peers. These responses were similar to the findings made by a study where interviews were conducted with children with an ICD and their parents [14].…”
Section: Communication Surrounding the Cardiomyopathysupporting
confidence: 81%
“…Specifically, some parents reported that their children struggled with ''feeling different'' and that they expressed desire to be more like their peers. These responses were similar to the findings made by a study where interviews were conducted with children with an ICD and their parents [14].…”
Section: Communication Surrounding the Cardiomyopathysupporting
confidence: 81%
“…Healthy college athletes have higher physical, emotional, and social functioning and quality-of-life scores than nonathletes, yet athletes sidelined with an injury score lower in all of these domains than both active athletes and nonathletes. 9 Many adolescents with ICDs 10 and their physicians 11 report restriction from sports and the resultant feeling of not being normal 10 as one of the most important negative aspects of their device. The basic principle of patient-centered care is that only the patient can determine what brings quality to his/her life.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, studies on children and adolescents with ICDs are limited. [7][8][9][10][11] DeMaso and colleagues 12 found changes in scores for anxiety, depression, family functioning, and quality of life (QoL) in pediatric patients with ICDs (20 patients). Sears and colleagues 13 examined a similar age group with ICDs and reported lower psychosocial and physical QoL scores compared with healthy children (60 patients).…”
mentioning
confidence: 99%